Effects of diets with soybean meal on the growth, digestibility, Phosphorus and Nitrogen excretion of juvenile rainbow trout Oncorhynchus mykiss - Cruz Castro, Carlos Agustín; Hernández Hernández, Luis Héctor; Fernández Araiza, Mario Alfredo; Ramírez Pérez, Teresa; Angeles López, Omar (HIDROBIOLÓGICA, 2017)
A feeding trial was performed to evaluate the inclusion of high levels of soybean meal as a substitute for fishmeal in diets for juvenile rainbow trout and determine the phosphorus and nitrogen excretion. Fishmeal was replaced with soybean meal at levels of 50, 75 and 100 % with an inclusion of 0.8 g of phytase per kg of diet (g kg-1 ), whereas a diet with 100% substitution was used without phytase. A commercial diet and one with 100% of fishmeal were used as controls. Diets were fed to triplicate groups of juveniles (4.12 ± 0.7 g, mean ± standard deviation) for a period of 50 days, and growth performance, P and N excretion and protein digestibility were determined at the end of this period. Data were analyzed with one-way ANOVA. The results showed that fish growth decreased when 100% of substitution was used, but diet with 75% of soybean meal did not affect growth. In addition, excretion values of P and N at this level of substitution were lower than those of the fish fed the control diets. The data suggest that diet with 75% soybean meal and 25% fishmeal might be used under practical conditions, as the growth performance observed on the juveniles fed such diet was similar to those of fish fed the commercial diet and the nutrient loading was reduced.